Phenomenology Study of Experiences and Reasons of Women Married Early in Kokop District, Bangkalan Madura - A’imMatun Nadhiroh; Fulatul Anifah; Fathiya Lutfil Yumni (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Early marriage has become a national problem in the field of reproductive health which we still encounter in the surrounding environment. Difficult economic conditions, lack of knowledge and family education so that children must be married at a young age. The purpose of this study is to explore the phenomenon of early marriage, both the experience and reasons for doing the early marriage.The method used in this study is a qualitative method using a phenomenological approach to explore in depth the experiences and reasons for early marriage. The research location is in Kokop, Bangkalan Regency, East Java. Data collection techniques were carried out by in-depth interviews with six women who had early marriage as main informants and one religious leader, and one health worker as triangulation. The data obtained were analyzed by describing and finding statements then grouped into the main points of the statements found.The results of the analysis of this study resulted in 4 themes discussed, namely the demands of parents, personal factors, culture and past experiences. The cause of this early marriage is due to arranged marriages and forced by parents, in addition to this reason those who do early marriage on consensual basis without knowing well the impact of early marriage. The experience of early marriage that has been experienced has made an important lesson that their children will not be married at an early age on the grounds that they are not ready and mature economically and healthily.The study of these three themes can provide benefits for understanding the experiences and reasons for early marriage, and we can prevent this from happening according to the reasons for each occurrence.